Photobleaching in STED nanoscopy and its dependence on the photon flux applied for reversible silencing of the fluorophore - Oracz, Joanna; Hell, Stefan (Scientific reports, 2017)
In STED (stimulated emission depletion) nanoscopy, the resolution and signal are limited by the fluorophore de-excitation efficiency and photobleaching. Here, we investigated their dependence on the pulse duration and power of the applied STED light for the popular 750 nm wavelength. In experiments with red- and orange-emitting dyes, the pulse duration was varied from the sub-picosecond range up to continuous-wave conditions, with average powers up to 200 mW at 80 MHz repetition rate, i.e. peak powers up to 1 kW and pulse energies up to 2.5 nJ. We demonstrate the dependence of bleaching on pulse duration, which dictates the optimal parameters of how to deliver the photons required for transient fluorophore silencing. Measurements with the dye ATTO647N reveal that the bleaching of excited molecules scales with peak power with a single effective order ~1.4. This motivates peak power reduction while maintaining the number of STED-light photons, in line with the superior resolution commonly achieved for nanosecond STED pulses. Other dyes (ATTO590, STAR580, STAR635P) exhibit two distinctive bleaching regimes for constant pulse energy, one with strong dependence on peak power, one nearly independent. We interpret the results within a photobleaching model that guides quantitative predictions of resolution and bleaching.
Gesehen am 25.10.2018